The Bank Soundness in Indonesia: Risk and Corporate Governance - Oppusunggu, Lis Sintha; Simbolon, Ika Pratiwi (Manunggal Halim Jaya, 2021)
This study aims to provide the evidence associated with the growth of corporate governance in crisis. This research is a type of literature study with secondary data (ROA and LDR) period January 2015–December 2019. The analysis is by using descriptive research with the support of theories and the findings from previous studies. Return on Assets (ROA) has increased and decreased for several periods and Loan to Deposit Ratio (LDR). Profitability with ROA decreased by 0.35% from 2.82% in January 2015 to 2.47% in December 2019. As measured by ROA, banking performance declines to make banks vulnerable to a crisis. Banks that have a high LDR potentially have liquidity risk. This study provides descriptive statistics that describe the potential of high LDR in the future since there's a sharp trend for the increasing value of LDR. LDR increased as much as 5.95% from 88.48% in January 2015 to 94.43% in December 2019. Liquidity risk continues to rise to make banks vulnerable to a crisis. This study provides several findings from previous research regarding standard corporate governance and risk governance in the financial crisis to mitigate those risks. Evaluating formal corporate management and risk governance can lead to optimal financial soundness.